Prediction on the special item result for female 100-meter athlete - Lu, G. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume III: Statistics and Managment in Sports., 2008)
The major influence factors in the scores of 100- meter races for female athletes shall be selected through succcssive regression analysis, investigation and interview, Delphi method, as well as professional characteristics. The inspecting index will be determined in order to establish the developing level models of 100- meter races for female athletes, as the results of this, the coach can controll the training proccss of the athletes in an objectivc way, and optimize the major index affecting and constraining the 100-meter race scores so that the athletes can create the excellent achievement as they can. The result shows that 1) The five major inspecting indices for 100- meter races for female athletes i.e. flying run 30m, step length, step frequency, ten-class standing long jump and 300m, have closely relation with the special item results. 2) Establishment of regression equation to forecast the results of China national master sportswomen, one class 100-meter races for female athletes.